BUILDING BRIDGES IN HEALTHCARE: A STUDY OF THE FACTORS AFFECTING EFFECTIVE WORKING RELATIONSHIPS AMONG MULTIDISCIPLINARY TEAMS IN GENERAL HOSPITAL PANDA, NASARAWA STATE - Ojo, Stephen S.; Nweke, Obieze N.; Ayesoro, Adesina S. (African Journal of Social and Behavioural Sciences, 2024)
The promotion of teamwork and industrial harmonization is crucial for the progress of different professions. Nevertheless, it is unavoidable that conflicts may arise due to the inherent human tendency towards disharmony when individuals with differing origins, professions, and attitudes collaborate towards a shared objective. This study evaluated factors affecting harmonious working relations among different professionals and cadres in the healthcare system using General Hospital Panda, Nasarawa State as a case study. Using quantitative cross-sectional survey design, respondents were enrolled from various departments of the hospital through stratified random sampling. Copies of questionnaire were distributed as the instrument of data collection. The findings indicate that harmonious working relations among different healthcare professionals in Nigeria are hindered by factors such as inter-professional conflict and rivalry, inadequate teamwork and collaboration, unclear professional hierarchies and role definitions, as well as challenges related to leadership and compensation. The study concludes that enhancing communication, resolving role ambiguity, facilitating interprofessional education, and establishing equitable compensation and working conditions are potential strategies that might build a collaborative and harmonious work environment among healthcare workers. It therefore recommends, among others, that the management should develop policies and procedures that promote fairness and equity in the workplace.